Diffusion weighted MR imaging - B. Ramsing; P. Corr (South African Journal of Radiology, 1998)
Diffusion weighted imaging (DWI) allows the measurement of molecular motion in tissue. This technique has significant clinical applications. Recent technological developments in fast MR imaging have brought diffusion imaging into clinical practice. This review will explain the physical principles, and current and future potential applications of diffusion imaging in medicine.